In-depth characterization of NK cell markers from CML patients who discontinued tyrosine kinase inhibitor therapy - Sanchez, María Belén; Vasconcelos Cordoba, Bianca; Pavlovsky, Carolina; Moiraghi, Beatriz; Varela, Ana; Custidiano, Rosario; Fernandez, Isolda; Freitas, María Josefina; Ventriglia, María Verónica; Bendek, Georgina; Mariano, Romina; Mela Osorio, María José; et al. (Frontiers in Immunology, 2023)
Treatment-free remission (TFR) in patients with chronic myeloid leukemia in chronic phase is considered a safe option if suitable molecular monitoring is available. However, the question arises as to which factors can contribute to the maintenance of TFR, and immunologic surveillance of the remaining leukemic cells is believed to be one of them. Argentina Stop Trial is an open-label, singlearm, multicenter trial assessing TFR after tyrosine kinase inhibitors interruption, that after more than 4 years showed a successful TFR rate of 63%. In this context, we set up an immunological study by flow cytometry in order to analyze specific NK cell subsets from peripheral blood patient samples both at the time of discontinuation as well as during the subsequent months. At the time of discontinuation, patients show a mature NK cell phenotype, probably associated to TKI treatment. However, 3 months after discontinuation, significant changes in several NK cell receptors occurred. Patients with a higher proportion of CD56 dim NK and PD-1 + NK cells showed better chances of survival. More interestingly, non-relapsing patients also presented a subpopulation of NK cells with features associated with the expansion after cytomegalovirus infection (expression of CD57 + NKG2C + ), and higher proportion of NKp30 and NKp46 natural cytotoxicity receptors, which resulted in greater degranulation and associated with better survival (p<0.0001). This NK cell subset could have a protective role in patients 2 This is a provisional file, not the final typeset article who do not relapse, thus further characterization could be useful for patients in sustained deep molecular response.